2009
DOI: 10.5483/bmbrep.2009.42.10.631
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock transcription factors and sensory placode development

Abstract: The heat shock transcription factor (HSF) family consists of at least three members in mammals and regulates expression of heat shock proteins in response to heat shock and proteotoxic stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…In contrast, HSF1 also induces cell death by upregulating proapoptotic genes in response to stress [22][23][24]. Furthermore, HSFs play critical roles in developmental processes such as gametogenesis and neurogenesis, in the maintenance of sensory organs and ciliated tissues, and in immune responses [25,26]. It has long been established that Hsp levels increase in a wide range of tumor types [27][28][29].…”
Section: Introductionmentioning
confidence: 90%
“…In contrast, HSF1 also induces cell death by upregulating proapoptotic genes in response to stress [22][23][24]. Furthermore, HSFs play critical roles in developmental processes such as gametogenesis and neurogenesis, in the maintenance of sensory organs and ciliated tissues, and in immune responses [25,26]. It has long been established that Hsp levels increase in a wide range of tumor types [27][28][29].…”
Section: Introductionmentioning
confidence: 90%
“…Mainly expressed in the human heart, brain, skeletal muscle, and pancreas [56], HSF4 has been shown to be required for the development and maintenance of sensory organs [5,57,58]. During this process, HSF4 either cooperates or competes with HSF1 for common target genes, including members of the Fibroblast Growth Factor (FGF) family, in a cell-specific manner in lens and olfactory epithelium [45,59].…”
Section: Hsf Structure Expression and Functionmentioning
confidence: 99%
“…7,19 Subsequently, disruption of the HSF1 gene was shown to result in altered expression of HSP and non-HSP genes in the tissues and to be required for development and maintenance, 20,21 suggesting that HSF1 regulates gene expression in unstressed cells. We found that HSF1 binds to the promoter of the NFATc2 gene in unstressed MEF cells and its expression is markedly reduced in HSF1-null cells.…”
Section: Non-hsp Proteostasis Pathwaysmentioning
confidence: 99%